2021
DOI: 10.2147/idr.s331890
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Influencing Multidrug-Resistant Tuberculosis and Validation of Whole-Genome Sequencing in Children with Drug-Resistant Tuberculosis

Abstract: Objective Pediatric tuberculosis (TB) is one of the top ten causes of death in children. Our study was to analyze influencing factors of multidrug-resistant tuberculosis (MDR-TB) and validation of whole-genome sequencing (WGS) used in children with drug-resistant TB (DR-TB). Methods All Mycobacterium tuberculosis (Mtb) strains were isolated from patients aged below 18 years old of Children’s Hospital of Chongqing Medical University, China. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…Reasons for consideration: First, although young children are immunocompromised and more susceptible to tuberculosis infection, they have a narrower contact surface and are more susceptible to direct transmission from adult patients, whereas older children have a wider contact surface but relatively higher immunity and relatively less risk of TB infection. [19][20][21] Second, the treatment methods for children of different age groups are basically the same, and under effective treatment and active preventive measures, so the age difference has little effect on the risk of DR-TB. Third, contact duration in the household and with individuals with tuberculosis are risk factors for tuberculosis, most cases of tuberculosis in children are caused by household contacts.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for consideration: First, although young children are immunocompromised and more susceptible to tuberculosis infection, they have a narrower contact surface and are more susceptible to direct transmission from adult patients, whereas older children have a wider contact surface but relatively higher immunity and relatively less risk of TB infection. [19][20][21] Second, the treatment methods for children of different age groups are basically the same, and under effective treatment and active preventive measures, so the age difference has little effect on the risk of DR-TB. Third, contact duration in the household and with individuals with tuberculosis are risk factors for tuberculosis, most cases of tuberculosis in children are caused by household contacts.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous treatment for TB is the strongest risk factor for development of DR-TB [32][33][34][35], treatment-naïve patients may also acquire drug resistance due to either transmission of resistant strains or spontaneous mutations. In our study we report strains resistant to some SLDs which are not being used to treat TB in Tanzania.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies (not including national anti-TB surveys) [7,32] have found that WGS testing of anti-TB drugs has the potential to provide comprehensive resistance detection much faster, with improved turnaround times, allowing for prompt appropriate treatment and associated patient and health-care benefits. [33].…”
Section: Discussionmentioning
confidence: 99%
“…WGS can thoroughly detect all genes related to drug resistance, which can provide valuable information for clinical treatment, particularly for MDR-TB (Votintseva et al, 2017;Doyle et al, 2018). WGS has also been studied for the identification of MDR-TB in children (Zhang et al, 2021). Compared with the conventional phenotypic drug susceptibility test (DST), it provides accurate results for both first-line and second-line anti-TB drugs.…”
Section: Diagnostic Challenges Of Drugresistant Tuberculosis In Childrenmentioning
confidence: 99%